Genome of a giant isopod, Bathynomus jamesi, provides insights into body size evolution and adaptation to deep-sea environment - Jianbo Yuan; Xiaojun Zhang; Qi Kou; Yamin Sun; Chengzhang Liu; Shihao Li; Yang Yu; Chengsong Zhang; Songjun Jin; Jianhai Xiang; Xinzheng Li; Fuhua Li (BMC Biology, 2022)
Abstract Background The deep-sea may be regarded as a hostile living environment, due to low temperature, high hydrostatic pressure, and limited food and light. Isopods, a species-rich group of crustaceans, are widely distributed across different environments including the deep sea and as such are a useful model for studying adaptation, migration, and speciation. Similar to other deep-sea organisms, giant isopods have larger body size than their shallow water relatives and have large stomachs and fat bodies presumably to store organic reserves. In order to shed light on the genetic basis of these large crustaceans adapting to the oligotrophic environment of deep-sea, the high-quality genome of a deep-sea giant isopod Bathynomus jamesi was sequenced and assembled. Results B. jamesi has a large genome of 5.89 Gb, representing the largest sequenced crustacean genome to date. Its large genome size is mainly attributable to the remarkable proliferation of transposable elements (84%), which may enable high genome plasticity for adaptive evolution. Unlike its relatives with small body size, B. jamesi has expanded gene families related to pathways of thyroid and insulin hormone signaling that potentially contribute to its large body size. Transcriptomic analysis showed that some expanded gene families related to glycolysis and vesicular transport were specifically expressed in its digestive organs. In addition, comparative genomics and gene expression analyses in six tissues suggested that B. jamesi has inefficient lipid degradation, low basal metabolic rate, and bulk food storage, suggesting giant isopods adopt a more efficient mechanism of nutrient absorption, storage, and utilization to provide sustained energy supply for their large body size. Conclusions Taken together, the giant isopod genome may provide a valuable resource for understanding body size evolution and adaptation mechanisms of macrobenthic organisms to deep-sea environments.